AN ANALYSIS OF LABOR PRODUCTIVITY IN SERBIA'S HOTEL INDUSTRY - Filipović, Vesna; Mašić, Saša; Radović, Nikica (The European Journal of Applied Economics, 2025)
Productivity, as a basic indicator of the success of a company's operations, shows the efficient use of labor in the work process. The subject of the research is labor productivity in the hotel industry of Serbia. The work aims to analyze the productivity of work in hotels from a natural and value aspect in 2022 and 2023. The analysis included hotels according to categorization (number of stars), size, and location of the facility. The research included 31 hotels, according to the categorization with three, four, and five stars. The financial data used in this analysis were taken from the financial reports of the observed business entities, on the website of the Agency for Business Registers. The obtained results show the growth of business income per employee in 2023 in nominal terms, and, at the same time, a decrease in real terms. Labor productivity shows an increase in hotels of the five-star category, as well as in small and large hotels.